(untitled) - Richard G Schlaadt (Englewood Cliffs, New Jersey)
This book offers a comprehensive survey of all types of drugs and their use.
Keywords: drug utilization - united states,pharmacology,psychotropic drugs,substance abuse - epidemiology - united states